Neutralization of SARS-CoV-2 Variants of Concern in Kidney Transplant Recipients after Standard COVID-19 Vaccination. Issue 1 (January 2022) - Benning, Louise; Morath, Christian; Bartenschlager, Marie; Nusshag, Christian; Kälble, Florian; Buylaert, Mirabel; Schaier, Matthias; Beimler, Jörg; Klein, Katrin; Grenz, Julia; Reichel, Paula; Hidmark, Asa; et al.
Visual Abstract: Abstract : Background and objectives: Antibody response after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination is impaired in kidney transplant recipients. Emerging variants, such as B.1.617.2 ( δ ), are of particular concern because of their higher transmissibility and partial immune escape. Little is known about protection against these variants in immunocompromised patients. Design, setting, participants, & measurements: In this prospective two-center study, antispike 1 IgG and surrogate neutralizing antibodies were measured in 173 kidney transplant recipients and 166 healthy controls with different vaccination schedules. In addition, different SARS-CoV-2 epitope antibodies from 135 vaccinated kidney transplant recipients were compared with antibodies in 25 matched healthy controls after second vaccination. In 36 kidney transplant recipients with seroconversion, neutralization against B.1.1.7 ( α ), B.1.351 ( β ), and B.1.617.2 ( δ ) was determined on VeroE6 cells and compared with neutralization in 25 healthy controls. Results: Kidney transplant recipients had significantly lower seroconversion rates compared with healthy controls. After the second vaccination, antispike 1, antireceptor-binding domain, and surrogate neutralizing antibodies were detectable in 30%, 27%, and 24% of kidney transplant recipients, respectively. This compares with 100%, 96%, and 100% in healthy controls, respectively ( P <0.001). Neutralization against B.1.1.7 was detectable in all kidney transplant recipients with seroconversion, with a median serum dilution that reduces infection of cells by 50% of 80 (interquartile range, 80–320). In contrast, only 23 of 36 (64%) and 24 of 36 (67%) kidney transplant recipients showed neutralization against B.1.351 and B.1.617.2, respectively, with median serum dilutions that reduce infection of cells by 50% of 20 (interquartile range, 0–40) and 20 (interquartile range, 0–40), respectively. Neutralization against different variants was significantly higher in healthy controls ( P <0.001), with all patients showing neutralization against all tested variants. Conclusions: Seroconverted kidney transplant recipients show impaired neutralization against emerging variants of concern after standard two-dose vaccination. Clinical Trial registry name and registration number: Observational study to assess the SARS-CoV-2 specific immune response in kidney transplant recipients (COVID-19 related immune response), DRKS00024668